Freedom of Choice About Incidental Findings Can Frustrate Participants' True Preferences. (23rd April 2015) - Viberg, Jennifer; Segerdahl, Pär; Langenskiöld, Sophie; Hansson, Mats G.
Abstract: Ethicists, regulators and researchers have struggled with the question of whether incidental findings in genomics studies should be disclosed to participants. In the ethical debate, a general consensus is that disclosed information should benefit participants. However, there is no agreement that genetic information will benefit participants, rather it may cause problems such as anxiety. One could get past this disagreement about disclosure of incidental findings by letting participants express their preferences in the consent form. We argue that this freedom of choice is problematic. In transferring the decision to participants, it is assumed that participants will understand what they decide about and that they will express what they truly want. However, psychological findings about people's reaction to probabilities and risk have been shown to involve both cognitive and emotional challenges. People change their attitude to risk depending on what is at stake. Their mood affects judgments and choices, and they over‐ and underestimate probabilities depending on whether they are low or high. Moreover, different framing of the options can steer people to a specific choice. Although it seems attractive to let participants express their preferences to incidental findings in the consent form, it is uncertain if this choice enables people to express what they truly prefer. In order to better understand the participants' preferences, we argue that future empirical work needs to confront the participant with the complexity of the uncertainty and the trade‐offs that are connected with the uncertain predictive value of genetic risk information.